Analysis Of The Factors Influencing The Decision Of Students In Choosing Majors In Labuhan Batu - Erni Wahyuni (CV. AFDIFAL MAJU BERKAH, 2022)
This study was conducted to target the students who are taking undergraduate education in a college in Labuhan Batu and conducted to determine and understand the factors that influence the decision of students in choosing a major. The independent variables examined in this study are the factors guidance, career expectations, perceptions and personal characteristics. The analysis of this research using the method of logistic regression analysis using a questionnaire with the number of respondents 280 people. Testing and analysis of the collected data was tested by using a software called SPSS (Statistical Product and Service Solutions). Testing conducted concluded that the guidance factors and personal characteristics significant positive effect on the decision of students in choosing a major. And also shows that there are variables that do not significantly influence the decision of students in choosing majors, among others, expectations and perception of career